INTERPRETATION OF THREE WHEAT CULTIVARS YIELD AND ITS COMPONENTS WITH REFERENCE TO SOWING DATES - Fergani, M. A.; El-Habbal S.; El-Temsah E. (Arab Universities Journal of Agricultural Sciences, 2014)
Two field experiments were carried out in Agric. Expt. Farm at Shalakan, Kaleobia Governorate, Cairo, Egypt during 2010/2011 and 2011/2012 growing seasons to study the response of some bread wheat cultivars to sowing dates. Each experiment included 15 treatments which were the combination between three wheat cultivars (Giza 168, Sakha 93 and Gemmiza 9) and five sowing dates (1st October, 16th October, 1st November, 16th November and 1st December). The experimental design used was split plot design in 6 replications. The data revealed that sowing dates and cultivars both significantly affected wheat yield and its components. Sowing on 1st November exhibited significant maximum plant height, number of spike/m2, main spike length and weight, grains number of main spike as well as grain, straw and biological yields as compared to early or late sowing in the season. Concerning wheat cultivars, Gemmiza 9 gave significantly highest yield and its components in comparison to Sakha 93 and Giza 168. The effect of the interaction between wheat cultivars and sowing dates were significantly differed in plant height, main spike length and weight, grain weight/spike as well as grain, straw and biological yields as well as GCPY. Gemmiza 9 exhibited the significant highest parameters when sown on 1st November as compared to the other studied two cultivars. The data revealed that sowing Gemmiza 9 wheat cultivar on 1st November was the most suitable environmental conditions for growing wheat in Kaluobia Governorate.